Measurement of Energy Correlators inside Jets and Determination of the Strong Coupling α_{S}(m_{Z}) - Hayrapetyan, A; Tumasyan, A; Adam, W; Andrejkovic, J W; Bergauer, T; Chatterjee, S; Damanakis, K; Dragicevic, M; Hussain, P S; Jeitler, M; Krammer, N; Li, A; et al. (Physical review letters, 2024)
Energy correlators that describe energy-weighted distances between two or three particles in a hadronic jet are measured using an event sample of sqrt[s]=13 TeV proton-proton collisions collected by the CMS experiment and corresponding to an integrated luminosity of 36.3 fb^{-1}. The measured distributions are consistent with the trends in the simulation that reveal two key features of the strong interaction: confinement and asymptotic freedom. By comparing the ratio of the measured three- and two-particle energy correlator distributions with theoretical calculations that resum collinear emissions at approximate next-to-next-to-leading-logarithmic accuracy matched to a next-to-leading-order calculation, the strong coupling is determined at the Z boson mass: α_{S}(m_{Z})=0.1229_{-0.0050}^{+0.0040}, the most precise α_{S}(m_{Z}) value obtained using jet substructure observables.